The Legal Certainty for Land Rights Holders Due to the Issuance Certificates Overlap of Certificates (Overlapping) on property Rights Certificate No. 60 Certificate Issued in 1956 and Certificate of Ownership No. 01729 Published in 2019 is Linked to Government Regulation No. 24 of 1997 on Land Registration. - Nurussabila Aulia; Dedy Hernawan (Journal of Law, Politic and Humanities, 2024)
Overlapping is a case of land that often occurs and accumulates in Indonesia, namely the certificates in the map placement overlap between one owner and another. This overlapping has happened so many times that cases have piled up, one of the causes of overlapping is that National Land Agency employees are negligent and irresponsible in carrying out their responsibilities in protecting and providing security to the community. The research method used is the Juridical-Normative approach method, the Juridical Qualitative analysis method, using Descriptive-Analytical research specifications by prioritizing legal objective theory. Errors that occur in practice are in the implementation of measurements, registration and mapping which are not carried out directly and in a systematic manner to obtain protection and certainty over ownership of land parcels and land boundaries so that parties obtain the benefits.